Convert Channel and Information Hiding in TCP/IP - Mr. Parikshith Nayaka S K, Mrs. Shobha Rani, Dr. Dayanand Lal, Dr. M Anand (International Journal of Control and Automation, 2020)
Confidentiality, Integrity and Availability are the primary objective of information Security. However, over the years information security researchers has found several techniques of data hiding on various systems that are widely used. One technique of data hiding covert channel, which emphasizes to hide information on a system, processes, TCP/IP Networking protocols which is against the computer policies and rules regulation. TCP/IP a protocol suite for specifying the standards for data transmission and communication between computers was found to be vulnerable to covert channel attack. These covert channels often utilize standard protocol loopholes often called as Network steganography. Further, we have developed a custom python script for POC purpose that can send, parse and detect covert channel which can be handy weapon for every forensic investigator. Besides the report, Practical approach has been taken into consideration for which a section for Proof of Concept is allocated at the end of this paper where covert channel over DNS as well as mitigating measure is demonstrated practically.